Real-time in vivo imaging reveals localised Nrf2 stress responses associated with direct and metabolism-dependent drug toxicity. Issue 1 (December 2017) - Forootan, Shiva; Mutter, Fiona; Kipar, Anja; Iwawaki, Takao; Francis, Ben; Goldring, Christopher; Park, B.; Copple, Ian
Abstract The transcription factor Nrf2 coordinates an adaptive response to chemical and oxidative stress characterised by the upregulated expression of cytoprotective target genes. In order to understand the mechanistic relevance of Nrf2 as a marker of drug-induced stress it is important to know if this adaptive response is truly localised in the context of organ-specific drug toxicity. Here, we address this knowledge gap through real-time bioluminescence imaging of transgenic Nrf2-luciferase (Nrf2-luc) reporter mice following administration of the metabolism-dependent hepatotoxin acetaminophen (APAP) or the direct nephrotoxin cisplatin. We detected localised bioluminescence in the liver (APAP) and kidneys (cisplatin)in vivo andex vivo, whilst qPCR, Taqman low-density array and immunoblot analysis of these tissues further revealed increases in the expression level of several endogenous Nrf2-regulated genes/proteins, including heme oxygenase 1 (Hmox1). Consistent with the toxic effects of APAP in the liver and cisplatin in the kidney, immunohistochemical analysis revealed the elevated expression of luciferase and Hmox1 in centrilobular hepatocytes and in tubular epithelial cells, respectively. In keeping with the role of reactive metabolite formation in APAP-induced chemical stress, both the hepatotoxicity and localised Nrf2-luc response were ameliorated by the cytochrome P450 inhibitor aminobenzotriazole. Together, these findings show that Nrf2 can reflect highly-localised cellular perturbations associated with relevant toxicological mechanisms.